Severe Wear and Pseudotumor Formation Due to Taper Mismatch in a Total Hip Arthroplasty: A Case Report. Issue 2 (April 2015) - Koper, M.C.; Mathijssen, N.M.C.; Witt, F.; Morlock, M.M.; Vehmeijer, S.B.W.
Abstract : Case: We describe the case of a seventy-six-year-old woman who had undergone bilateral total hip arthroplasty with Zweymüller-Metasul prostheses in 1996. After a fall sixteen years after the index procedures, radiographs suggested a taper fracture of the left total hip arthroplasty. However, revision surgery showed pseudotumor formation, with no evidence of taper fracture. Analysis of the prosthesis showed massive wear of the male stem taper caused by a mismatch between the stem taper and the head taper. Conclusion: This case vividly demonstrates how taper size mismatch can cause dramatic metal wear and increased release of metal ions, resulting in pseudotumor formation.